Solid electrolytic capacitor element and solid electrolytic capacitor

By designing a solid electrolyte layer composed of nitrogen, sulfur, carbon and oxygen in a specific proportion of the solid electrolyte capacitor, the problem of ESR increase in high temperature and high humidity environment is solved, and the conductivity stability and capacity improvement of the capacitor is achieved.

CN120380561APending Publication Date: 2025-07-25PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380086779.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-21
Filing Date
2023-12-19
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The equivalent series resistance (ESR) of solid electrolytic capacitors increases in high temperature and high humidity environments, and it is difficult for the prior art to effectively suppress it.

Method used

A solid electrolyte layer including nitrogen element N, sulfur element S, carbon element C and oxygen element O is used, with an N/S mass ratio of more than 0.30 and less than 1.00 and less than 1.00 and less than the second part thickness is 15 μm or more and less than 42 μm. By filling the pores of the pores of the dielectric layer and protruding from the main surface of the anode body, the conductive polymer composition of the cathode part is adjusted to balance the ratio of the cationic agent and the anionic agent.

Benefits of technology

It effectively suppresses the ESR increase of solid electrolytic capacitors in high temperature and high humidity environments, maintains stable conductivity, prevents deterioration of the cathode lead-out layer, and improves the stability and capacity of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120380561A_ABST
    Figure CN120380561A_ABST
Patent Text Reader

Abstract

A solid electrolytic capacitor element includes: an anode body having a porous portion at least in a surface layer; a dielectric layer covering at least a portion of the anode body; and a cathode part covering at least a part of the dielectric layer. The cathode portion includes a solid electrolyte layer covering at least a portion of the dielectric layer. The solid electrolyte layer contains nitrogen element N, sulfur element S, carbon element C, and oxygen element O, and has a first portion filled into the pores of the porous portion in the anode body having the dielectric layer, and a second portion protruding from the main surface of the anode body having the dielectric layer. The mass ratio N / S of elemental nitrogen (N) to elemental sulfur (S) in the second portion is 0.30-1.00 (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a solid electrolytic capacitor element and a solid electrolytic capacitor. Background Art

[0002] A solid electrolytic capacitor includes a solid electrolytic capacitor element, a resin exterior or a case for sealing the solid electrolytic capacitor element, and an external electrode electrically connected to the solid electrolytic capacitor element. The solid electrolytic capacitor element includes, for example, an anode body, a dielectric layer formed on the surface of the anode body, and a cathode portion covering at least a part of the dielectric layer. The cathode portion includes a conductive polymer (for example, a conjugated polymer and a dopant) covering at least a part of the dielectric layer. The conductive polymer is also referred to as a solid electrolyte.

[0003] Patent Document 1 proposes a method for manufacturing a solid electrolytic capacitor, which is a method for manufacturing a solid electrolytic capacitor including a capacitor element having a dielectric layer and a solid electrolyte layer. The formation of the solid electrolyte layer has a process of sequentially performing the following processes: a first process of coating a first conductive polymer solution in which fine particles of a conductive polymer are dispersed and drying to form a first conductive polymer layer; a second process of coating a covering solution containing at least one selected from aromatic sulfonic acids or their salts on the first conductive polymer layer and drying, the aromatic sulfonic acid having a carboxyl group and a hydroxyl group, or two carboxyl groups in one molecule; and a third process of coating a second conductive polymer solution in which fine particles of a conductive polymer are dispersed and drying to form a second conductive polymer layer. As the covering solution, a solution containing a cation of an amine compound is used.

[0004] Patent Document 2 proposes a conductive polymer capacitor, characterized in that the atomic number ratio α / (Al + N + S + α) of the electrode cross-section is 0.01 or less (α is the cation atomic number constituting the oxidant, and Al, N, and S are the atomic numbers of aluminum, nitrogen, and sulfur, respectively).

[0005] Prior Art Documents

[0006] Patent Documents

[0007] Patent Document 1: International Publication No. 2014 / 087617

[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 2009-54925 Summary of the Invention

[0009] Problems to be Solved by the Invention

[0010] When the solid electrolyte layer contains nitrogen (N) element derived from an amine compound or the like and sulfur (S) element derived from a sulfonic acid compound or the like, in some cases, the equivalent series resistance (ESR) of the solid electrolytic capacitor may increase after being exposed to a high-temperature and high-humidity environment.

[0011] Solution to the problem

[0012] The first aspect of the present disclosure relates to a solid electrolytic capacitor element, which includes: an anode body having a porous portion at least on the surface layer; a dielectric layer covering at least a part of the aforementioned anode body; and a cathode portion covering at least a part of the aforementioned dielectric layer.

[0013] The aforementioned cathode portion includes a solid electrolyte layer covering at least a part of the aforementioned dielectric layer.

[0014] The aforementioned solid electrolyte layer contains nitrogen element N, sulfur element S, carbon element C, and oxygen element O, and has: a first portion filled in the pores of the aforementioned porous portion filled in the aforementioned anode body having the aforementioned dielectric layer, and a second portion protruding from the main surface of the aforementioned anode body having the aforementioned dielectric layer.

[0015] The mass ratio of nitrogen element N to sulfur element S in the aforementioned second portion: N / S is 0.30 or more and 1.00 or less.

[0016] The second aspect of the present disclosure relates to a solid electrolytic capacitor, which includes at least one of the above solid electrolytic capacitor elements.

[0017] Effects of the invention

[0018] It is possible to suppress an increase in the ESR of the solid electrolytic capacitor after being exposed to a high-temperature and high-humidity environment. Brief description of the drawings

[0019] Figure 1 It is a schematic cross-sectional view of a solid electrolytic capacitor according to an embodiment of the present disclosure.

[0020] Figure 2 It is a schematic front view when observing the solid electrolytic capacitor element from one main surface side.

[0021] Figure 3 It is when observing in the direction of the arrow Figure 2 A schematic cross-sectional view of the solid electrolytic capacitor element at the III-III line of the cross-section. Detailed description of the invention

[0022] The new features of the present invention are described in the appended claims, but the present invention relates to both the constitution and the content. In combination with other objects and features of the present invention, it can be better understood through the following detailed description with reference to the drawings.

[0023] When forming a solid electrolyte layer using a treatment liquid containing a conductive polymer, in order to form a solid electrolyte layer with a certain thickness, it is necessary to repeatedly coat the treatment liquid multiple times. However, due to the charge repulsion of anionic groups such as dopants contained in the conductive polymer, it is difficult for the conductive polymer to adhere to the solid electrolyte layer. If a cationic agent such as an amine compound or a salt of a cationic agent and an anionic agent such as a sulfonic acid compound is attached to the solid electrolyte layer as in Patent Document 1, the conductive polymer easily adheres when the treatment liquid is applied. In the solid electrolyte layer thus formed, it contains N element derived from the cationic agent and S element derived from the anionic agent. However, it has been clarified that when the solid electrolytic capacitor is exposed to a high-temperature and high-humidity environment, the mass ratio of nitrogen element N to sulfur element S in the solid electrolyte layer: the balance of N / S affects the ESR of the solid electrolytic capacitor.

[0024] It is considered that the reason for the increase in the ESR of the solid electrolytic capacitor is that in a high-temperature and high-humidity environment, due to the component derived from the cationic agent in the solid electrolyte layer, the solid electrolyte layer swells due to moisture absorption and the resistivity increases. The cathode part sometimes includes a solid electrolyte layer and a cathode lead-out layer covering the solid electrolyte layer. In a high-temperature and high-humidity environment, due to the action of components such as those derived from the anionic agent in the solid electrolyte layer, the resistivity of the cathode lead-out layer (for example, the metal particle-containing layer contained in the cathode lead-out layer) sometimes increases. Thus, it is also considered that the ESR of the solid electrolytic capacitor increases.

[0025] In view of the above situation, (1) the solid electrolytic capacitor element of the first aspect of the present disclosure includes: an anode body having at least a porous part on the surface layer; a dielectric layer covering at least a part of the anode body; and a cathode part covering at least a part of the dielectric layer. The cathode part includes a solid electrolyte layer covering at least a part of the dielectric layer. The solid electrolyte layer contains nitrogen element N, sulfur element S, carbon element C, and oxygen element O, and has: a first part filled in the pores of the porous part of the anode body having the dielectric layer, and a second part protruding from the main surface of the anode body having the dielectric layer. And the mass ratio of nitrogen element N to sulfur element S in the second part: N / S is 0.30 or more and 1.00 or less. Hereinafter, the solid electrolytic capacitor element may sometimes be referred to as a capacitor element.

[0026] In the present disclosure, by having the N / S ratio within the above-mentioned range, it is possible to reduce the moisture absorption amount of the solid electrolyte layer when the solid electrolytic capacitor is exposed to a high-temperature and high-humidity environment, and it is possible to suppress an increase in resistivity. In addition, it is possible to suppress an increase in the resistivity of the cathode lead-out layer (including the metal particle layer, etc.) caused by components derived from anionic agents such as sulfonic acid compounds. Therefore, it is possible to suppress an increase in the ESR of the solid electrolytic capacitor when exposed to a high-temperature and high-humidity environment. It should be noted that the reason for the suppression of the increase in resistivity is considered to be that the N-containing component derived from the cationic agent interacts with the S-containing component derived from the anionic agent, thereby reducing the moisture absorption amount or reducing the influence on the cathode lead-out layer. In contrast, when the N / S ratio is less than 0.30, the resistivity of the cathode lead-out layer (including the metal particle layer, etc.) increases. When the N / S ratio exceeds 1.00, the moisture absorption amount of the solid electrolyte layer increases, resulting in an increase in resistivity. Thus, in either case, the ESR of the solid electrolytic capacitor increases when exposed to a high-temperature and high-humidity environment.

[0027] (2) In the above (1), the mass ratio of nitrogen element N in the aforementioned second part to the total amount of carbon element C, oxygen element O, and sulfur element S: N / (C + O + S) can be 0.033 or more and 0.050 or less. When the N / (C + O + S) ratio is within such a range, it is easy to ensure a certain thickness of the solid electrolyte layer, it is possible to suppress a decrease in the conductivity of the conductive polymer, thereby suppressing an increase in ESR. In addition, it is easy to achieve a balance in the amounts of the cationic agent and the anionic agent with respect to the conductive polymer, and it is possible to further suppress an increase in the resistivity of the solid electrolyte layer and the cathode lead-out layer (including the metal particle layer, etc.) when exposed to a high-temperature and high-humidity environment, and it is possible to suppress fluctuations in the ESR of the solid electrolytic capacitor.

[0028] (3) In the above (1) or (2), the maximum thickness of the second part can be 15 μm or more and 42 μm or less. When the solid electrolytic capacitor is exposed to a high-temperature and high-humidity environment, the conductive polymer deteriorates or de-doping occurs, and the conductivity easily decreases. Such a decrease in conductivity easily occurs from the outside of the solid electrolyte layer. By having the maximum thickness of the second part be 15 μm or more, even if the conductivity of the outer part of the solid electrolyte layer decreases, the high conductivity is maintained in the inner part, and it is possible to suppress an increase in ESR. By making the maximum thickness of the second part be 42 μm or less, a higher capacitance can be obtained.

[0029] (4) In any one of the above (1) to (3), the anode body has an anode lead-out portion including a first end portion and a cathode formation portion including a second end portion. In a cross-section perpendicular to the direction from the first end portion of the capacitor element to the second end portion at an arbitrary position of the portion on the first end portion side of the solid electrolyte layer, the ratio of the thickness T1 of the second portion formed at the corner of the anode body to the thickness T2 of the second portion formed at the central portion of the anode body: T1 / T2 may be 0.8 or more and 1.7 or less. By reducing the deviation of the thickness of the solid electrolyte layer over the entire surface of the cathode formation portion of the anode body, the deviation of the conductivity of the solid electrolyte layer when the solid electrolytic capacitor is exposed to a high-temperature and high-humidity environment is suppressed, an increase in ESR, a decrease in capacitance, etc. are suppressed, and the quality of the solid electrolytic capacitor is made more stable.

[0030] (5) In any one of the above (1) to (4), the cathode portion includes a conductive carbon layer covering at least a part of the solid electrolyte layer. In a high-temperature and high-humidity environment, the cathode lead-out layer (especially the metal particle-containing layer) is liable to deteriorate due to components derived from the sulfonic acid compound contained in the solid electrolyte layer and the conductivity decreases. However, in the present disclosure, by making the N / S ratio of the second portion within a specific range, the deterioration of the cathode lead-out layer (metal particle-containing layer, etc.) is suppressed, high conductivity is ensured, and thus ESR can be suppressed to a low level.

[0031] (6) In any one of the above (1) to (5), the second portion may include a conjugated polymer and a dopant. The conjugated polymer may include monomer units corresponding to thiophene compounds, and the dopant has a sulfo group. In the case where the second portion includes such a conjugated polymer and a dopant, by setting the N / S ratio within the above range, an increase in ESR in a high-temperature and high-humidity environment can be further suppressed.

[0032] (7) In the present disclosure, there is also provided a solid electrolytic capacitor including at least one capacitor element according to any one of the above (1) to (6).

[0033] Hereinafter, including the above (1) to (7), the solid electrolytic capacitor and the capacitor element of the present disclosure will be described more specifically. As long as at least one selected from the constituent elements described below can be combined technically, it can be arbitrarily combined with at least one of the above (1) to (7) of the solid electrolytic capacitor of the present disclosure.

[0034] [Solid electrolytic capacitor]

[0035] The solid electrolytic capacitor includes one or two or more capacitor elements.

[0036] [Capacitor element]

[0037] The capacitor element includes: an anode body; a dielectric layer covering at least a part of the anode body; and a cathode portion covering at least a part of the dielectric layer. The cathode portion includes a solid electrolyte layer covering at least a part of the dielectric layer.

[0038] (Anode body)

[0039] The anode body can include, for example, a valve metal, an alloy containing a valve metal, and a compound containing a valve metal (intermetallic compound, etc.). These materials can be used alone or in combination of two or more. As the valve metal, aluminum, tantalum, niobium, titanium, etc. can be cited.

[0040] The anode body can be a foil (anode foil) of a valve metal, an alloy containing a valve metal, or a compound containing a valve metal, or a formed body (porous formed body) of particles of a valve metal, an alloy containing a valve metal, or a compound containing a valve metal, or a sintered body (porous sintered body) thereof.

[0041] The anode body has an anode lead-out portion including a first end portion and a cathode formation portion including a second end portion opposite to the first end portion. A cathode portion including a solid electrolyte layer is formed on the surface of the cathode formation portion of the anode body. The anode lead-out portion is used, for example, for electrically connecting to an external electrode on the anode side. An anode lead terminal can also be connected to the anode lead-out portion.

[0042] The anode body has a porous portion at least on the surface layer. The porous portion includes many fine pores. Through the porous portion, the anode body has a fine uneven shape at least on the surface, the surface area becomes larger, and a high capacitance can be obtained. The porous portion can be formed on a part of the surface layer of the anode body or on the entire surface layer. In the case where the anode body is an anode foil, the porous portion can be formed, for example, at least on the surface layer of the cathode formation portion, or in addition to being formed on the surface layer of the cathode formation portion, it can also be formed on at least a part of the surface layer of the anode lead-out portion. In the case where the anode body is a porous formed body or a porous sintered body, the entire anode body can constitute the porous portion.

[0043] In the case where the anode body is an anode foil, the porous portion is formed by roughening at least a part of the surface of a base material (for example, a metal foil) containing a valve metal corresponding to the cathode formation portion. The roughening can also be performed by an etching treatment, etc. The etching treatment can be performed by electrolytic etching or by chemical etching.

[0044] The anode body generally has six surfaces that define the shape of the anode body. Sometimes, the surface (usually a pair of surfaces) that occupies the largest area among these surfaces is called the main surface, and the surfaces other than the main surface are called end surfaces. There are corner portions between adjacent surfaces. For example, in the case where the anode body is an anode foil, there is a pair of main surfaces that occupy most of the area of the anode foil and end surfaces existing between the pair of main surfaces.

[0045] In this specification, sometimes the direction from the first end portion toward the second end portion in the flat state of the anode body (such as an anode foil) is called the length direction of the anode body. The direction from the first end portion side toward the second end portion side refers to the direction parallel to the straight line direction connecting the center of the end surface of the first end portion and the center of the end surface of the second end portion. Sometimes this direction is called the length direction of the anode body or the capacitor element. In addition, sometimes the direction perpendicular to the length direction and the thickness direction of the anode body (or capacitor element) is called the width direction of the anode body (or capacitor element).

[0046] (Dielectric layer)

[0047] The dielectric layer is an insulating layer that functions as a dielectric. The dielectric layer is formed by anodizing the valve metal on the surface of the anode body by using chemical conversion treatment or the like. In the dielectric layer formed on the surface of the anode foil having a porous portion, the surface of the dielectric layer has a fine uneven shape according to the shape of the surface of the porous portion.

[0048] The dielectric layer can also be formed using a material that functions as a dielectric layer. The dielectric layer contains, for example, an oxide of a valve metal as such a material. For example, when tantalum is used as the valve metal, the dielectric layer contains Ta2O5, and when aluminum is used as the valve metal, the dielectric layer contains Al2O3. However, the dielectric layer is not limited to these specific examples.

[0049] (Cathode portion)

[0050] The cathode portion at least includes a solid electrolyte layer that covers at least a part of the dielectric layer. The portion of the solid electrolyte layer on the second end portion side of the anode body (in other words, the cathode forming portion) is formed with the dielectric layer interposed therebetween. The cathode portion generally includes a solid electrolyte layer that covers at least a part of the dielectric layer and a cathode lead layer that covers at least a part of the solid electrolyte layer. Hereinafter, the solid electrolyte layer and the cathode lead layer will be described.

[0051] (Solid electrolyte layer)

[0052] The solid electrolyte layer contains N element, S element, C element and O element. The solid electrolyte layer is divided into a first part filled in the pores of the porous part filled into the anode body having a dielectric layer and a second part protruding from the main surface of the anode body having a dielectric layer. Moreover, the mass ratio of N element to S element in the second part: N / S is 0.30 or more and 1.00 or less. By setting the N / S ratio within such a range, an increase in ESR after the solid electrolytic capacitor is exposed to a high-temperature and high-humidity environment can be alleviated.

[0053] The solid electrolyte layer is composed of a solid electrolyte (in other words, a conductive polymer). The conductive polymer contains a conjugated polymer and a dopant. The conductive polymer may also contain additives as needed. In addition, the solid electrolyte layer contains at least one selected from the group consisting of the components derived from the cation agent and the components derived from the anion agent as described above. The N element sometimes also originates from the conjugated polymer, but mostly originates from the cation agent contained in the treatment liquid. The S element sometimes also originates from the conjugated polymer or the dopant, but mostly originates from the anion agent contained in the treatment liquid. Therefore, it can be said that the N / S ratio represents the balance between the cation agent and the anion agent in the second part of the solid electrolyte layer. It should be noted that the N element and the S element may also be contained in the first part. In the second part that occupies most of the solid electrolyte layer, by setting the N / S ratio within the above range, a remarkable effect of suppressing an increase in ESR can be obtained.

[0054] The N / S ratio is 0.30 or more, may be 0.35 or more, may also be 0.40 or more or 0.41 or more. The N / S ratio is 1.00 or less, may be 0.97 or less, may also be 0.95 or less. From the viewpoint of suppressing the ESR after the solid electrolytic capacitor is exposed to a high-temperature and high-humidity environment to a lower level, the N / S ratio may be 0.80 or less, may also be 0.77 or less. The N / S ratio can be, for example, 0.30 or more and 1.00 or less, 0.35 or more and 0.97 or less, or 0.40 or more and 0.95 or less.

[0055] Most of the C element and O element contained in the solid electrolyte layer originate from the conductive polymer. The N / (C + O + S) ratio may be 0.033 or more, may also be 0.034 or more. From the viewpoint of suppressing the ESR after the solid electrolytic capacitor is exposed to a high-temperature and high-humidity environment to a lower level, the N / (C + O + S) ratio may be 0.035 or more. The N / (C + O + S) ratio may be 0.050 or less, may also be 0.046 or less. The N / (C + O + S) ratio can be 0.033 or more and 0.050 or less, 0.034 or more and 0.050 or less, or 0.035 or more and 0.050 or less.

[0056] The content ratio of the mass standard of each element in the second part is obtained by performing elemental mapping using energy dispersive X-ray spectroscopy (EDX) on an image obtained by a scanning electron microscope (SEM) of the exposed capacitor element or solid electrolytic capacitor. The N / S ratio and the N / (C + O + S) ratio are obtained from the obtained content ratio. Elemental mapping is performed on a rectangular region (region A) where the length of the first side is 10 μm or more and 20 μm or less, and the length of the second side orthogonal to the first side is 12 μm or more and 25 μm or less. The first side of region A may be parallel or non-parallel to the width direction or the thickness direction of the capacitor element. The second side of region A may be parallel or non-parallel to the thickness direction or the width direction of the capacitor element. The shortest distance between region A and the main surface of the anode body may be 0 μm or more and 5 μm or less. It should be noted that the shortest distance between region A and the main surface of the anode body is the shortest distance between the average main surface of the anode body determined in the above cross-sectional image and region A. The content ratio of each element is obtained by measuring and averaging a plurality of regions A of the exposed cross-section. It is preferable that the shortest distances between each region A and the main surface of the anode body both satisfy the above ranges.

[0057] The sample for photographing the SEM image is prepared according to the following steps. The capacitor element or solid electrolytic capacitor is buried in a curable resin and the curable resin is cured. The cured product is wet-polished or dry-polished to expose a cross-section parallel to the thickness direction of the cathode portion (a cross-section capable of confirming the laminated state of each layer of the cathode portion). The exposed cross-section is smoothed by ion milling to obtain a sample for photographing. It should be noted that when the length of the region where the solid electrolyte layer is formed in the direction parallel to the length direction of the capacitor element is set to 1, the cross-section is set to the cross-section at a position from the end on the first end side of the region where the solid electrolyte layer is formed to 0 to 0.05 (0 or more and 0.05 or less).

[0058] The maximum thickness of the second part may be 15 μm or more, or may be 16 μm or more. The maximum thickness of the second part may be 42 μm or less, or may be 40 μm or less. For example, the maximum thickness of the second part may be 15 μm or more and 42 μm or less, or 16 μm or more and 42 μm or less. When the maximum thickness of the second part is in such a range, even if a part on the cathode lead-out layer side of the second part deteriorates in a high-temperature and high-humidity environment, a certain degree of high conductivity can be ensured on the part on the first part side, thereby further suppressing an increase in ESR. The maximum thickness of the second part is the maximum value of the thickness of the second part obtained in the above cross-sectional image.

[0059] In a cross-section perpendicular to the direction from the first end portion toward the second end portion of the capacitor element, at an arbitrary position of a portion on the first end portion side of the anode body of the solid electrolyte layer, the ratio of the thickness T1 of the second portion formed at the corner of the anode body to the thickness T2 of the second portion formed at the central portion of the anode body: T1 / T2 can be 0.8 or more, or can be 0.9 or more. The T1 / T2 ratio can be 1.7 or less, can be 1.5 or less, or can be 1.2 or less. For example, the T1 / T2 ratio can be 0.8 or more and 1.7 or less, or 0.9 or more and 1.7 or less. When the T1 / T2 ratio is in such a range, the deviation of the change in the conductivity of the solid electrolyte layer when the solid electrolytic capacitor is exposed to a high-temperature and high-humidity environment is suppressed, and the increase in ESR is further suppressed. In addition, since the decrease in the thickness of the solid electrolyte layer at the corner is suppressed, the occurrence of product defects due to short circuits is suppressed.

[0060] (First portion) The first portion includes at least a first conductive polymer layer, and may also include a first conductive polymer layer and a second conductive polymer layer. The first portion can be a single layer or can be composed of multiple layers. When the first portion is composed of multiple layers, the types, compositions, contents, etc. of the conductive polymers, additives, etc. contained in each layer can be the same or different. However, the first conductive polymer layer and the second conductive polymer layer do not necessarily need to be in a layer form. For example, it can also be a state where the first conductive polymer is attached to the surface of the dielectric layer.

[0061] Examples of the first conductive polymer and the second conductive polymer contained in each conductive polymer layer include known conductive polymers used in solid electrolytic capacitors, such as conjugated polymers (π-conjugated polymers, etc.) and dopants. The first conductive polymer can also include self-doped conductive polymers.

[0062] Examples of the conjugated polymer include polymers having a basic skeleton of polypyrrole, polythiophene, polyaniline, polyfuran, polyacetylene, polyphenylene, polyphenylene vinylene, polyacene, and polythiophene vinylene. The above polymers only need to contain at least one monomer unit constituting the basic skeleton. The monomer unit also includes a monomer unit having a substituent. The above polymers also include homopolymers and copolymers of two or more monomers. For example, polythiophene includes poly(3,4-ethylenedioxythiophene) (PEDOT), etc.

[0063] When using a conjugated polymer containing monomer units corresponding to a thiophene compound, the initial ESR can be suppressed to a low level, and a high capacity can be easily obtained. As the thiophene compound, a compound having a thiophene ring and capable of forming a repeating structure of the corresponding monomer unit can be cited. The thiophene compound can form a repeating structure of the monomer unit by connecting at the 2-position and 5-position of the thiophene ring.

[0064] The thiophene compound can have a substituent at at least one of the 3-position and 4-position of the thiophene ring, for example. The substituent at the 3-position and the substituent at the 4-position can be connected to form a ring fused to the thiophene ring. As the thiophene compound, for example, a thiophene having a substituent at at least one of the 3-position and 4-position, an alkylenedioxythiophene compound (such as an ethylenedioxythiophene compound, etc., C 2-4 alkylenedioxythiophene compounds, etc.) can be cited. The alkylenedioxythiophene compound also includes an alkylenedioxythiophene compound having a substituent in the alkyl part.

[0065] As the substituent, an alkyl group (such as a methyl group, an ethyl group, etc., C 1-4 alkyl groups, etc.), an alkoxy group (such as a methoxy group, an ethoxy group, etc., C 1-4 alkoxy groups, etc.), a hydroxyl group, a hydroxyalkyl group (such as a hydroxymethyl group, etc., hydroxy C 1-4 alkyl groups, etc.) can be cited, but are not limited to these. When the thiophene compound has two or more substituents, the substituents can be the same or different.

[0066] A conjugated polymer containing at least monomer units corresponding to a 3,4-ethylenedioxythiophene compound (such as 3,4-ethylenedioxythiophene (EDOT), etc.) (such as PEDOT, etc.) can also be used. The conjugated polymer containing at least monomer units corresponding to EDOT can contain only monomer units corresponding to EDOT, or can contain, in addition to these monomer units, monomer units corresponding to thiophene compounds other than EDOT.

[0067] The conjugated polymer can be used alone or in combination of two or more.

[0068] The weight-average molecular weight (Mw) of the conjugated polymer is not particularly limited, and is, for example, 1000 or more and 1000000 or less.

[0069] It should be noted that in this specification, the weight-average molecular weight (Mw) is a value in terms of polystyrene measured by gel permeation chromatography (GPC). It should be noted that GPC is usually measured using a polystyrene gel column and water / methanol (volume ratio 8 / 2) as the mobile phase.

[0070] As the dopant, for example, at least one selected from the group consisting of anions and polyanions is used.

[0071] Examples of the anion include, but are not particularly limited to, sulfate ion, nitrate ion, phosphate ion, borate ion, organic sulfonate ion, carboxylate ion, etc. Examples of the dopant that generates sulfonate ion include aromatic sulfonic acid compounds (such as p-toluenesulfonic acid and naphthalenesulfonic acid).

[0072] Examples of the polyanion include, but are not limited to, polymeric sulfonic acids and polymeric carboxylic acids of the polymer type. Examples of the polymeric sulfonic acid of the polymer type include polyvinylsulfonic acid, polystyrenesulfonic acid, polyallylsulfonic acid, polyacrylic acid-based sulfonic acid, and polymethacrylic acid-based sulfonic acid. Examples of the polymeric carboxylic acid of the polymer type include polyacrylic acid and polymethacrylic acid. The polyanion also includes polyester sulfonic acid and phenol sulfonic acid novolac resin, etc. However, the polyanion is not limited to these.

[0073] From the viewpoint of easily suppressing dedoping, it is advantageous to use a polyanion having relatively high heat resistance and electron-withdrawing property among the polyanions (such as polymeric sulfonic acid of the polymer type).

[0074] In the first part, the anionic group (such as sulfo group and carboxyl group) of the dopant can be included in a free form, anionic form, or salt form, or can be included in a form bonded or interacting with the conjugated polymer. In this specification, including all these forms, it is sometimes simply referred to as "anionic group", "sulfo group", or "carboxyl group", etc.

[0075] The amount of the dopant contained in the first conductive polymer layer or the second conductive polymer layer is, for example, 10 parts by mass or more and 1000 parts by mass or less, or can be 50 parts by mass or more and 200 parts by mass or less with respect to 100 parts by mass of the conjugated polymer.

[0076] The first conductive polymer layer and the second conductive polymer layer can also be formed by attaching a treatment liquid (such as a dispersion or solution) containing a conductive polymer (conjugated polymer and) to the dielectric layer and then drying it. Examples of the dispersion medium (or solvent) include at least one selected from the group consisting of water and organic solvents. The treatment liquid can also contain other components (such as additives). For example, a treatment liquid containing a conductive polymer (such as PEDOT), a dopant (such as a polyanion like polystyrenesulfonic acid), and additives as needed can also be used to form the solid electrolyte layer.

[0077] The first conductive polymer layer can be formed by polymerizing a precursor containing a conjugated polymer on a dielectric layer using a treatment liquid containing the precursor of the conjugated polymer and a dopant. The polymerization can be carried out by at least one of chemical polymerization and electrolytic polymerization. Examples of the precursor of the conjugated polymer include monomers, oligomers, or prepolymers. In the case of using a treatment liquid containing a precursor of a conjugated polymer, an oxidizing agent is used to polymerize the precursor. The oxidizing agent can be included as an additive in the treatment liquid. Alternatively, the oxidizing agent can be coated on the anode body before or after bringing the treatment liquid into contact with the anode body having a dielectric layer formed thereon. Examples of such an oxidizing agent include compounds capable of generating Fe 3+ (such as iron sulfate), persulfates (such as sodium persulfate and ammonium persulfate), and hydrogen peroxide. The oxidizing agent can be used alone or in combination of two or more.

[0078] Sometimes, the treatment liquid for forming the first part (such as the first conductive polymer layer) is referred to as the first treatment liquid. The step of forming the first conductive polymer layer by impregnation and polymerization (or drying) in the first treatment liquid can be carried out once or repeated multiple times. Similarly, the step of forming the second conductive polymer layer can be carried out once or repeated multiple times. In the case of repeating multiple times, in each time, the conditions such as the composition and viscosity of the treatment liquid can be the same or at least one condition can be changed.

[0079] The first conductive polymer layer and the second conductive polymer layer can each be a single layer or composed of multiple layers. In the case where the first layer is composed of multiple layers, the conductive polymers contained in each layer can be the same or different.

[0080] (Second part)

[0081] The second part contains, for example, a second conductive polymer (such as a conjugated polymer and a dopant). It may also contain at least a second conductive polymer layer. The second part (or the second conductive polymer layer) can be a single layer or composed of multiple layers. In the case where the second part (or the second conductive polymer layer) is composed of multiple layers, the types, compositions, contents, etc. of the conductive polymers, additives, etc. contained in each layer can be the same or different.

[0082] Regarding the second conductive polymer constituting the second part or the second conductive polymer layer, reference can be made to the description of the second conductive polymer of the first part. The conjugated polymer contained in the second part preferably contains monomer units corresponding to thiophene compounds. Additionally, the dopant preferably has a sulfo group. In the case where the second part contains such a conjugated polymer and a dopant, by setting the N / S ratio within the above range, the ESR can be suppressed to a lower level.

[0083] In the second part, the anionic groups (sulfonic groups, carboxyl groups, etc.) of the dopant can be included in a free form, an anionic form, or a salt form, or can be included in a form bonded to or interacting with the conjugated polymer. In this specification, all these forms are sometimes simply referred to as "anionic groups", "sulfonic groups", or "carboxyl groups", etc.

[0084] The amount of the dopant contained in the second layer is, for example, 10 parts by mass or more and 1000 parts by mass or less, or can be 50 parts by mass or more and 200 parts by mass or less with respect to 100 parts by mass of the conjugated polymer.

[0085] The second part (or the second conductive polymer layer) is formed, for example, by treating an anode body having a first part (or a first conductive polymer layer) formed thereon through a dielectric layer with a treatment liquid (second treatment liquid) containing an anionic agent and a cationic agent, or a salt thereof, and then treating it with a treatment liquid (third treatment liquid) containing a second conductive polymer. At least one of the anionic agent and the cationic agent contains N element. At least one of the anionic agent and the cationic agent contains S element. The second treatment liquid may further contain a surface conditioner.

[0086] More specifically, the second part (or the second conductive polymer layer) is formed by treating the above-mentioned anode body with the second treatment liquid, drying it, then treating it with the third treatment liquid and drying it. The process A of treating and drying with the second treatment liquid and the process B of treating and drying with the third treatment liquid can be repeated multiple times. The mode of performing process A and process B (repeating mode, etc.) can be determined according to the N / S ratio or the N / (C + O + S) ratio. For example, process A and process B can be alternately repeated. In addition, process B can be performed once or multiple times after performing process A once or multiple times. Process B can also be performed multiple times after performing process A multiple times, and they can be alternately repeated. In process A, after the treatment and drying with the second treatment liquid, washing with water and drying can be further performed.

[0087] The N / S ratio and the N / (C + O + S) ratio can be adjusted, for example, by selecting or adjusting at least one selected from the group consisting of the use of a surface modifier, the concentration of the surface modifier in the second treatment liquid, the anionic agent, the cationic agent or the concentration of its salt in the second treatment liquid, the number of times of each of step A and step B, the implementation of water washing in step A, and the repetition pattern of step A and step B. In addition to these, the N / (C + O + S) can be further adjusted by the type of the second conductive polymer, the ratio of the amount of the dopant to the conjugated polymer, and the like. Further, the maximum thickness of the second part can be adjusted, for example, by selecting or adjusting at least one selected from the concentration of the anionic agent, the cationic agent or its salt in the second treatment liquid, the number of times of each of step A and step B, and the implementation of water washing in step A. The T1 / T2 ratio can be adjusted, for example, by adjusting the type and concentration of the surface modifier, the type of the liquid medium used in the second treatment liquid, the drying conditions of the coating film of the second treatment liquid, and the like.

[0088] The cationic agent and the anionic agent are different from the surface modifier, respectively. As the surface modifier, for example, a surfactant can be cited. As the cationic agent and the anionic agent, components that are not surfactants are used, respectively.

[0089] The first conductive polymer layer and the layer formed using the third treatment liquid generally contain an anionic dopant, and this dopant easily exists on the surface of each layer. That is, the surface of each layer is easily negatively charged, so it is difficult to overlap with each layer to form a layer containing the second conductive polymer. By applying the second treatment liquid containing the cationic agent to the first conductive polymer layer or the layer formed using the third treatment liquid, the film-forming property of the second conductive polymer layer can be improved. In addition, by including the anionic agent in the second treatment liquid, the film covering repair property of the dielectric layer can be improved, and the dissociation property of the cationic agent can be improved, which is advantageous for improving the film-forming property.

[0090] (Cationic agent)

[0091] The cationic agent having a cationic group is not particularly limited as long as it can generate cations in a dissociated state. As the cationic agent, for example, it can be a metal compound (such as an inorganic base such as metal hydroxide), and preferably an organic compound containing N element (such as an organic base). As the cationic group of the cationic agent of the organic compound, an amino group (primary amino group, secondary amino group, tertiary amino group, etc.) and a quaternary ammonium group are preferred. Such cationic groups also include salts of amino groups and salts of quaternary ammonium groups. The second part or the second conductive polymer layer can contain one type of cationic agent or two or more types of cationic agents.

[0092] Among the cationic agents, cationic agents having an amino group as a cationic group (amine compounds, etc.) are preferred. As amine compounds, amines having 1 or more and 3 or less substituents on the nitrogen atom (primary amines, secondary amines, and tertiary amines), diamines having 1 or 2 alkyl groups on the nitrogen atom, etc. can be exemplified. The substituents are, for example, selected from the group consisting of alkyl groups, cycloalkyl groups, and aryl groups. The alkyl group, cycloalkyl group, and aryl group may each further have a substituent (for example, at least 1 selected from the group consisting of a hydroxyl group and an alkoxy group).

[0093] As the above diamine, diaminoalkanes, diamino cycloalkanes (diaminocyclohexane and other diamino C 5-8 cycloalkanes, etc.), diaminoarenes (diaminobenzene, diaminonaphthalene, and other diamino C 6-14 arenes, etc.) can be exemplified. As the diaminoalkane, diaminoc 2-14 alkane or diaminoc 4-12 alkane, etc. can be listed. Specific examples of the diaminoalkane include 1,4-diaminobutane, 1,6-diaminohexane, 1,8-diaminooctane, and 1,10-diaminodecane.

[0094] As the amine, at least one selected from the group consisting of primary amines and tertiary amines can be used. As the tertiary amine, N,N-diC 1-10 alkyl-N-C 4-16 alkylamine (N,N-dimethylhexylamine, N,N-dimethyloctylamine, N,N-diethyloctylamine, etc.), N,N-diC 4-16 alkyl-N-C 1-10 alkylamine, triC 4-16 alkylamine, etc. can be exemplified.

[0095] The second part or the second conductive polymer layer may contain a cationic agent in any form of an amine compound, a cation corresponding to the amine compound, a quaternary ammonium compound, and a salt of a cation. For example, in the second part or the second conductive polymer layer, the cationic agent may form a salt with an anionic agent or may interact with a dopant.

[0096] (Anionic agent)

[0097] As the anionic agent, for example, at least one selected from the group consisting of anions and polyanions exemplified as dopants for the first conductive polymer and the second conductive polymer can be used. An anionic agent containing an S element is particularly preferably used. Further, from the viewpoint of suppressing the dedoping of the first conductive polymer and the second conductive polymer, as the anionic agent, an anionic agent different from the dopants of the first conductive polymer and the second conductive polymer is preferably used. From the same viewpoint, as the anionic agent, an anionic agent having a lower electron-withdrawing property than the dopants of the respective conductive polymers can be used.

[0098] In the second treatment liquid, the anionic group of the anionic agent can be contained in any form selected from the above-mentioned anionic groups, anions corresponding to the above-mentioned anionic groups, and salts of anions.

[0099] As the anionic agent, for example, a sulfonic acid compound (such as aliphatic sulfonic acid, alicyclic sulfonic acid, aromatic sulfonic acid, etc.) can be used.

[0100] From the viewpoint of suppressing the corrosion of the valve-acting metal constituting the anode body, an anionic agent (first anionic agent) containing a sulfo group (first anionic group) and a second anionic group with a lower electron-withdrawing property than the sulfo group can be used. As the first anionic agent, for example, an anionic agent having a sulfo group and a carboxyl group, and an anionic agent having a sulfo group and a hydroxyl group can be cited. As the first anionic agent, for example, aliphatic compounds (such as sulfosuccinic acid), aromatic compounds (such as sulfobenzoic acid, sulfosalicylic acid, disulfosalicylic acid, sulfophthalic acid, sulfoisophthalic acid, sulfoterephthalic acid, naphtholsulfonic acid, etc.) can be cited. As the first anionic agent, a polymer containing a sulfo group and a second anionic group can be used.

[0101] As the first anionic agent of the polymer (high molecular compound), for example, a copolymer (p1) containing at least a monomer unit having a first anionic group and a monomer unit having a second anionic group, and a polymer (p2) containing at least a monomer unit having a first anionic group and a second anionic group can be exemplified. These polymers can further contain other copolymerizable monomer units.

[0102] As the monomer units that are the basis of the above monomer units, for example, aliphatic vinyl monomer units such as ethylene and propylene, aromatic vinyl monomer units such as styrene, and diene monomer units such as butadiene and isoprene can be cited.

[0103] The Mw of the polymer is, for example, 5000 or more and 500000 or less, and can also be 10000 or more and 200000 or less.

[0104] The first anionic agent can be used alone or in combination of two or more.

[0105] The first anionic agent can be used in combination with the second anionic agent as needed. As the second anionic agent, for example, monomer compounds among the anions and polyanions described as the dopants of the first layer can be used. The second anionic agent can be any of aliphatic compounds, alicyclic compounds, and aromatic compounds. The second anionic agent can be used alone or in combination of two or more.

[0106] As the second anionic agent, examples include the above-mentioned sulfonic acid compounds, acid phosphyloxy polyoxyalkylene glycol monoacrylate of carboxylic acids such as acryloyloxyethyl acid phosphate, methacryloyloxyethyl acid phosphate, etc. (acid phosphyloxy polyethylene glycol mono(meth)acrylate (P(=O)(OH)2-(O-CH2CH2) n -O-C(=O)-CR=CH2) (n is an integer of 2 or more and 10 or less, R is a hydrogen atom or a methyl group), etc.), aliphatic phosphonic acids (vinylphosphonic acid, etc.), aromatic phosphonic acids (phenylphosphonic acid, etc.), carboxylic acids [aliphatic carboxylic acids (propionic acid, butyric acid, hexanoic acid, etc. C 2-10 alkane carboxylic acids, adipic acid, etc. C 4-12 alkane dicarboxylic acids, etc.), alicyclic carboxylic acids (carboxycyclohexane, etc. carboxy C 5-8 cycloalkane, cyclohexanedicarboxylic acid, etc. dicarboxy C 5-8 cycloalkane, etc.), aromatic carboxylic acids (benzoic acid, etc. carboxy C 6-14 arene, salicylic acid, etc. carboxyhydroxy C 6-14 arene, phthalic acid, isophthalic acid, terephthalic acid, naphthalenedicarboxylic acid, etc. dicarboxy C 6-14 arene, etc.), phenolic compounds (phenol, hydroxytoluene, vinylphenol, hydroxyvinyltoluene, etc.), hydroxyalkyl esters of the above-mentioned carboxylic acids (for example, hydroxyethyl acrylate, hydroxyethyl methacrylate, etc. hydroxy C 1-4 alkyl esters), etc. As the sulfonic acid compound, examples include aliphatic sulfonic acids (methanesulfonic acid, etc. C 1-6 alkane sulfonic acids, etc.), alicyclic sulfonic acids (cyclohexanesulfonic acid, etc. C 5-8 cycloalkane sulfonic acids, etc.), aromatic sulfonic acids (benzenesulfonic acid, styrenesulfonic acid, etc. C 6-14 arene sulfonic acids, etc.), etc.

[0107] As the second anionic agent, an anionic agent having two or more anionic groups can be used. As such a second anionic agent, examples include a second anionic agent having a phosphoric acid group and a carboxyl group (for example, 2-(dihydroxyphosphinyloxy)acrylic acid), a second anionic agent having a phosphonic acid group and a carboxyl group (for example, phosphonacryloyl acid, 2-methyl-3-phosphonacryloyl acid), etc.

[0108] (Surface conditioner)

[0109] Surface conditioners include, for example, leveling agents and defoaming agents. From the viewpoint of spreading the second treatment liquid containing the surface conditioner over the entire surface of the cathode forming portion of the anode body, as the surface conditioner, a surface conditioner having a leveling effect is preferred. As the surface conditioner, a surfactant is preferably used.

[0110] The surfactant can be any of nonionic surfactants and ionic surfactants. The surfactant has a hydrophilic group and a hydrophobic group. Ionic surfactants include cationic surfactants, anionic surfactants, and amphoteric surfactants. The surfactant can be used alone or in combination of two or more.

[0111] Examples of nonionic surfactants include ether type (polyether type etc.), ester-ether type (fatty acid polyethylene glycol ester, fatty acid polyoxyethylene sorbitan ester etc.), ester type (glycerol fatty acid ester, sorbitan fatty acid ester, sucrose fatty acid ester etc.), or alkanolamide type (fatty acid alkanolamide etc.) nonionic surfactants. Examples of polyether type nonionic surfactants include polyether type nonionic surfactants having a polyoxyalkylene chain such as a polyoxyethylene chain (polyoxyethylene alkyl ether, polyoxyethylene alkyl phenyl ether, polyoxyethylene polyoxypropylene glycol etc.). The nonionic surfactant can have a halogen atom. Halogen atoms include fluorine atom, chlorine atom, bromine atom, and iodine atom. Among them, fluorine atom is preferred.

[0112] Examples of cationic surfactants include, for example, alkylamine salt type (monoalkylamine salt, dialkylamine salt, trialkylamine salt etc.), quaternary ammonium salt type (alkyltrimethylammonium halide, dialkyldimethylammonium halide, alkylbenzalkonium chloride etc.) cationic surfactants.

[0113] Examples of anionic surfactants include, for example, carboxylic acid type, sulfonic acid type, sulfate ester type, and phosphate ester type anionic surfactants. Examples of carboxylic acid type anionic surfactants include aliphatic monocarboxylates, polyoxyethylene alkyl ether carboxylates, N-acyl sarcosinates, N-acyl glutamates etc. Examples of sulfonic acid type anionic surfactants include dialkyl sulfosuccinates, alkane sulfonates, α-olefin sulfonates, alkylbenzene sulfonates, naphthalene sulfonic acid-formaldehyde condensates, alkyl naphthalene sulfonates, N-methyl-N-acyl taurates etc. Examples of sulfate ester type anionic surfactants include alkyl sulfates, polyoxyethylene alkyl ether sulfates, oil sulfate salts etc. Examples of phosphate ester type anionic surfactants include alkyl phosphates, polyoxyethylene alkyl ether phosphates, polyoxyethylene alkyl phenyl ether phosphates etc.

[0114] Examples of amphoteric surfactants include carboxybetaine type (alkyl betaine, fatty acid amide propyl betaine etc.), 2-alkylimidazoline derivative type (2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolium betaine etc.), glycine type (alkyl diethylenetriaminoacetic acid, dialkyl diethylenetriaminoacetic acid etc.), amine oxide type (alkyl amine oxide etc.) amphoteric surfactants.

[0115] When a nonionic surfactant is used, the pot life of the second treatment liquid is inhibited from shortening, and dedoping of the conductive polymer can be inhibited. From the viewpoint of more easily promoting the adhesion of the conductive polymer to the surface of the anode body, a cationic surfactant or an amphoteric surfactant can be used. From the viewpoint of easily suppressing the volatilization of the cationic agent described later, an anionic surfactant can be used.

[0116] The content rate of the surface conditioner in the second part can be 0.01% by mass or more and 30% by mass or less, or can be 0.10% by mass or more and 15% by mass or less. When the content rate of the surface conditioner is in such a range, the surface conditioner can be more uniformly distributed over the entire surface of the cathode forming part, and it is easy to reduce the deviation in the thickness of the second part. Moreover, the resistivity of the second part can be suppressed to a low level, which is advantageous in suppressing an increase in ESR.

[0117] (Other)

[0118] The first part and the second part can each further contain at least one selected from the group consisting of known additives and known conductive materials other than the conductive polymer, as needed. As the conductive material, for example, at least one selected from the group consisting of conductive inorganic materials such as manganese dioxide and TCNQ complex salts can be cited. Additionally, a layer for improving adhesion can be interposed between the dielectric layer and the first part (or the first conductive polymer layer).

[0119] (Cathode lead-out layer)

[0120] The cathode lead-out layer only needs to have at least a first layer that contacts the solid electrolyte layer and covers at least a part of the solid electrolyte layer, and can also have a first layer and a second layer that covers at least a part of the first layer.

[0121] Examples of the first layer include a layer containing conductive particles, a metal foil, etc. Examples of the conductive particles include at least one selected from conductive carbon and metal powder. The cathode part (more specifically, the cathode lead-out layer) can contain a layer containing metal powder (such as a metal particle layer). In this case, in a high-temperature and high-humidity environment, due to the components derived from the anionic agent, the resistivity of the cathode lead-out layer (such as the metal particle layer) is likely to increase. In the present disclosure, by setting the N / S ratio of the second part within a specific range, high conductivity of the cathode lead-out layer (such as the metal particle layer) can be ensured, and an increase in ESR in a high-temperature and high-humidity environment can be suppressed. The cathode lead-out layer can be constituted by, for example, a layer containing conductive carbon (carbon layer) as the first layer and a layer containing metal powder (such as a metal particle layer) or a metal foil as the second layer.

[0122] In the case where the cathode lead-out layer includes a metal foil or a metal particle-containing layer, the entire cathode lead-out layer may be constituted by the metal foil or the metal particle-containing layer. Further, at least one of the first layer and the second layer may be constituted by the metal particle-containing layer.

[0123] Examples of the conductive carbon include graphite (artificial graphite, natural graphite, etc.).

[0124] The layer containing metal powder as the second layer can be formed, for example, by laminating a composition containing metal powder on the surface of the first layer. Examples of such a second layer include a metal particle-containing layer formed using a paste containing metal powder and a resin binder. As the resin binder, a thermoplastic resin may be used, but a thermosetting resin such as an imide-based resin or an epoxy resin is preferably used. From the viewpoint of easily obtaining high conductivity of the second layer, silver-containing particles can be used as the metal powder. Examples of the silver-containing particles include silver particles and silver alloy particles. The second layer may contain one kind of silver-containing particles or may contain two or more kinds in combination. The silver particles may contain a small amount of impurities.

[0125] In the case where a metal foil is used as the first layer, the kind of the metal is not particularly limited. The metal foil is preferably a valve-acting metal (aluminum, tantalum, niobium, etc.) or an alloy containing a valve-acting metal. If necessary, the surface of the metal foil can be roughened. A chemical conversion coating film can be provided on the surface of the metal foil, or a coating film of a metal (dissimilar metal) or a non-metal different from the metal constituting the metal foil can be provided. Examples of the dissimilar metal and non-metal include a metal such as titanium or a non-metal such as carbon (conductive carbon, etc.).

[0126] The coating film of the above-mentioned dissimilar metal or non-metal (for example, conductive carbon) can also be used as the first layer, and the above-mentioned metal foil can be used as the second layer.

[0127] The cathode lead-out layer is formed by a known method according to its layer constitution. For example, in the case where the cathode lead-out layer includes a metal foil as the first layer or the second layer, the metal foil is laminated so as to cover at least a part of the solid electrolyte layer or the first layer, thereby forming the first layer or the second layer. The first layer containing conductive particles is formed, for example, by applying a conductive paste or a liquid dispersion containing conductive particles and, if necessary, a resin binder (water-soluble resin, curable resin, etc.) to the surface of the solid electrolyte layer. The second layer containing metal powder is formed, for example, by applying a paste containing metal powder and a resin binder to the surface of the first layer. During the formation process of the cathode lead-out layer, drying treatment, heat treatment, etc. can also be performed if necessary.

[0128] (Separator)

[0129] In the case where a metal foil is used for the cathode lead-out layer, a separator can also be disposed between the metal foil and the anode foil. There is no particular limitation on the separator. For example, a nonwoven fabric containing fibers of cellulose, polyethylene terephthalate, vinylon, polyamide (such as aliphatic polyamide, aromatic polyamide such as aramid, etc.) can be used.

[0130] (Other)

[0131] The solid electrolytic capacitor includes at least one capacitor element. The solid electrolytic capacitor can be of a wound type, or can be any one of a chip type or a stacked type. For example, the solid electrolytic capacitor can also include a plurality of stacked capacitor elements. In addition, the solid electrolytic capacitor can also include two or more wound capacitor elements. The structure of the capacitor element can be selected according to the type of the solid electrolytic capacitor.

[0132] In the capacitor element, the cathode lead-out layer can be electrically connected to one end portion of the cathode lead terminal. For example, a conductive adhesive is applied to the cathode lead-out layer of the cathode lead terminal, and the cathode lead-out layer is joined by means of the conductive adhesive. The anode lead-out portion of the anode body can be electrically connected to one end portion of the anode lead terminal. The other end portions of the anode lead terminal and the cathode lead terminal are respectively led out from the resin outer package or the housing. The other end portions of the respective terminals exposed from the resin outer package or the housing are used for soldering to the substrate on which the solid electrolytic capacitor is to be mounted, etc. In addition, not limited to the case of leading out lead terminals, at least one end surface of the anode portion and the cathode portion can also be exposed from the outer surface of the sealing body and electrically connected to an external electrode.

[0133] The capacitor element is sealed using a resin outer package or a housing. For example, the capacitor element and the material resin of the outer package (for example, an uncured thermosetting resin and a filler) can be accommodated in a mold, and the capacitor element can be sealed with a resin outer package by a transfer molding method, a compression molding method, etc. At this time, the anode lead terminal connected to the anode lead led out from the capacitor element and the portions on the other end side of the cathode lead terminal are respectively exposed from the mold. In addition, the capacitor element can also be accommodated in a bottomed housing in such a manner that the portions on the other end side of the anode lead terminal and the cathode lead terminal are located on the opening side of the bottomed housing, and the opening of the bottomed housing is sealed with a sealing body, thereby forming a solid electrolytic capacitor.

[0134] Figure 1It is a cross-sectional schematic view of an electrolytic capacitor according to an embodiment of the present disclosure. The solid electrolytic capacitor 1 includes a capacitor element 11, a resin outer package 12 that seals the capacitor element 11, and an anode terminal 13 and a cathode terminal 14 that are respectively exposed to the outside of the resin outer package 12. The capacitor element 11 includes an anode body 2, a dielectric layer 3 that covers the second end portion side of the anode body 2, and a cathode portion 15 that covers the dielectric layer 3. The portion of the anode body 2 where the cathode portion 15 (especially the solid electrolyte layer 4) is formed is the cathode formation portion, and the portion where the cathode portion 15 is not formed is the anode lead-out portion. The anode terminal 13 is electrically connected to the anode lead-out portion of the anode body 2. The cathode terminal 14 is electrically connected to the cathode portion 15. The resin outer package 12 has a substantially rectangular parallelepiped shape, and thus, the solid electrolytic capacitor 1 also has a substantially rectangular parallelepiped shape.

[0135] The anode body 2 and the cathode portion 15 face each other with the dielectric layer 3 therebetween. The cathode portion 15 has a solid electrolyte layer 4 that covers the dielectric layer 3 and a cathode lead-out layer 5 that covers the solid electrolyte layer 4. The cathode lead-out layer 5 in the illustrated example has a two-layer structure and has a carbon layer 5a that contacts the solid electrolyte layer 4 and a metal particle-containing layer 5b that covers the surface of the carbon layer 5a.

[0136] In the region on the cathode portion 15 side in the anode lead-out portion of the anode body 2 that protrudes from the cathode portion 15, an insulating separation portion 16 is formed so as to cover the surface of the anode body 2 in a strip shape, restricting the contact between the cathode portion 15 and the anode body 2. The first end portion of the anode body 2 that protrudes from the cathode portion 15 is electrically connected to one end portion 13a of the anode terminal 13 by welding or the like. On the other hand, the cathode lead-out layer 5 formed on the outermost layer of the cathode portion 15 is electrically connected to one end portion 14a of the cathode terminal 14 by a conductive adhesive 17 (for example, a mixture of a thermosetting resin and metal particles). The other end portion 13b of the anode terminal 13 and the other end portion 14b of the cathode terminal 14 are respectively led out from different side surfaces of the resin outer package 12 and extend in an exposed state to a main flat surface (the lower surface in Figure 1 ). The exposed portions of the respective terminals on this flat surface are used for welding or the like to a substrate (not shown) on which the solid electrolytic capacitor 1 should be mounted.

[0137] The dielectric layer 3 is formed on a part of the surface of the conductive material that constitutes the anode body 2. Specifically, the dielectric layer 3 can be formed by anodizing the surface of the conductive material that constitutes the anode body 2. Therefore, the dielectric layer 3 is formed along the surface of the anode body 2 (including the holes in the inner surface and the inner wall surfaces of the depressions).

[0138] Figure 2 It is a schematic front view when observing the capacitor element from one main surface side. Figure 3 It is when observing in the direction of the arrow Figure 2Schematic cross-sectional view of the III-III line cross-section (cross-section G) of the capacitor element. The thicknesses T1 and T2 of the solid electrolyte layer are obtained, for example, by the following steps.

[0139] The ratio T1 / T2 is obtained in the cross-section G of the cathode portion 15 perpendicular to the direction from the first end portion E1 to the second end portion E2 of the capacitor element 11 (sometimes referred to as the length direction of the anode body 2 or the capacitor element 11). Here, the cross-section G is formed at an arbitrary position in the portion of the anode body 2 on the first end portion E1 side. The portion of the cathode portion 15 on the first end portion E1 side means the portion from the end portion on the first end portion E1 side of the cathode portion 15 to the position of the length L / 2 when the length of the cathode portion 15 in the length direction of the capacitor element 11 is L. In Figure 2 the portion of the cathode portion 15 on the first end portion E1 side corresponds to the upper half of the cathode portion 15.

[0140] In Figure 3 a cross-section G of the capacitor element 11 perpendicular to the length direction of the capacitor element 11 at the III-III line of the portion of the cathode portion 15 on the first end portion E1 side is shown. The III-III line corresponds to an arbitrarily selected position in the portion of the cathode portion 15 on the first end portion E1 side. It should be noted that in Figure 3 the hatching indicating the cross-section is omitted.

[0141] In the above cross-section G, a pair of main surfaces Ms of the anode body 2 that is the anode foil and a pair of end surfaces Es located at the ends of the pair of main surfaces Ms are observed. Since there are corner portions between each main surface Ms and each end surface Es, four corner portions can be confirmed in the above cross-section G of the anode body 2. Imaginary straight lines L1 and L2 are drawn by extending the lines corresponding to each main surface Ms outward, and a straight line passing through the vertex of the corner portion at an angle of 45° with respect to the straight line L1 or L2 is drawn. For the point where this straight line intersects the outer edge of the solid electrolyte layer 4, the distances D11, D12, D13, and D14 between this point and the vertex of the corner portion are set as the thicknesses of the solid electrolyte layer 4 at each corner portion. Then, T1 is obtained by averaging the values of these 4 distances.

[0142] In the above cross-section G, when the width of the anode body 2 corresponding to the length of the line segment equivalent to the main surface Ms is set as W, a center line CL is drawn from a position at a distance of W / 2 from each end surface Es. The center line CL passes through the midpoint of the line segment corresponding to each main surface Ms of the anode body 2. The distances D21 and D22 between the intersection point of the center line CL and the outer edge of the solid electrolyte layer 4 and the midpoint of the above line segment are respectively set as the thicknesses of the solid electrolyte layer at the central portion of the main surface Ms. T2 is obtained by averaging the values of these 2 distances.

[0143] [Embodiment]

[0144] Hereinafter, the present invention will be specifically described based on examples and comparative examples, but the present invention is not limited to the following examples.

[0145] "Solid electrolytic capacitor E1"

[0146] A solid electrolytic capacitor was produced according to the following procedures, and its characteristics were evaluated.

[0147] (1) Process for preparing an anode body

[0148] An anode body was produced by roughening both surfaces of an aluminum foil (thickness: 100 μm) serving as a base material by etching.

[0149] (2) Process for forming a dielectric layer

[0150] A part of the first end portion side of the anode body was immersed in a chemical conversion solution, and a DC voltage of 70 V was applied for 20 minutes to form a dielectric layer containing alumina.

[0151] (3) Process for forming a solid electrolyte layer

[0152] While stirring, 3,4-ethylenedioxythiophene monomer was added to an aqueous solution of polystyrenesulfonic acid (Mw: 75000), and then an oxidizing agent (iron(III) sulfate and sodium persulfate) was added for chemical oxidative polymerization. The resulting polymerization solution was filtered using an ion exchange device to remove impurities, thereby obtaining a solution containing PEDOT as a first conductive polymer and polystyrenesulfonic acid (PSS) as a dopant.

[0153] Pure water was added to the obtained solution, homogenized using a high-pressure homogenizer, and further filtered using a filter, thereby preparing a first treatment liquid in a dispersed state.

[0154] After the anode body having the dielectric layer formed in the above (2) was immersed in the first treatment liquid, it was taken out from the first treatment liquid and further dried at 120 °C for a time of 10 minutes or more and 30 minutes or less. By further repeating the immersion in the first treatment liquid and drying once each, a first conductive polymer layer was formed so as to cover the surface of the dielectric layer 3.

[0155] Dissolve a salt of an ester-type nonionic surfactant (surface conditioner), a cationic agent (N,N-dimethyloctylamine), and an anionic agent (sulfophthalic acid) in distilled water to prepare a second treatment solution. The amount of the surface conditioner in the second treatment solution is 0.5% by mass, and the concentration of the above salt is 2.5% by mass. After immersing the anode body having the first layer formed thereon in the second treatment solution, take it out and dry it at 100 °C for 3 minutes. Then, immerse the dried anode body in a third treatment solution having the same composition as the first treatment solution, take it out, and dry it at 120 °C for a time of 10 minutes or more and 30 minutes or less. Repeat the immersion and drying in the second treatment solution and the immersion and drying in the third treatment solution alternately 4 times. In this way, a second conductive polymer layer containing N element and S element is formed. It should be noted that most of the second part is composed of the second conductive polymer layer. In this way, a solid electrolyte layer having a first conductive polymer layer and a second conductive polymer layer (or a first part and a second part) is formed so as to cover the surface of the dielectric layer.

[0156] (4) Process for forming the cathode lead layer

[0157] Immerse the anode body obtained in the above (3) in a dispersion liquid in which graphite particles are dispersed in water. After taking it out from the dispersion liquid, dry it, thereby forming a carbon layer 5a on the surface of the solid electrolyte layer. The drying is carried out at a temperature of 130 °C or more and 180 °C or less for a time of 10 minutes or more and 30 minutes or less.

[0158] Next, apply a silver paste containing silver particles and a binder resin (epoxy resin) on the surface of the carbon layer 5a, and heat it at a temperature of 150 °C or more and 200 °C or less for a time of 10 minutes or more and 60 minutes or less, thereby curing the binder resin to form a metal particle-containing layer 5b. In this way, a cathode lead layer 5 composed of a carbon layer 5a and a metal particle-containing layer 5b is formed.

[0159] As described above, the capacitor element 11 is manufactured.

[0160] (5) Assembly of the solid electrolytic capacitor

[0161] Bond the cathode lead layer 5 of the capacitor element 11 obtained in the above (4) to one end portion 14a of the cathode terminal 14 using a conductive adhesive 17. Bond a portion on the first end portion side of the anode body 2 protruding from the capacitor element 11 to one end portion 13a of the anode terminal 13 by laser welding.

[0162] Next, by transfer molding, form a resin outer package 12 made of an insulating resin around the capacitor element 11. At this time, the other end portion 13b of the anode terminal 13 and the other end portion 14b of the cathode terminal 14 are in a state of being led out from the resin outer package 12.

[0163] Thus, the solid electrolytic capacitor E1 is completed. A total of 20 solid electrolytic capacitors E1 are fabricated in the same manner as described above.

[0164] (6) Evaluation

[0165] Using the fabricated solid electrolytic capacitors, the following evaluations are performed.

[0166] (a) Element ratio of the second part

[0167] According to the described procedure, elemental mapping of the second part is performed using EDX based on the SEM image of the cross-section of the solid electrolytic capacitor, and the mass ratios of N element, S element, C element, and O element are obtained. The N / S ratio and N / (C + O + S) ratio are calculated from the mass ratios of the respective elements.

[0168] It should be noted that the elemental mapping using EDX is performed under the conditions of frame: 128 and resolution: 256×200.

[0169] (b) Maximum thickness of the second part and thickness ratio T1 / T2

[0170] According to the described procedure, the maximum value of the thickness of the second part in each solid electrolytic capacitor and the thickness ratio T1 / T2 of the second part are obtained. Then, for the 20 solid electrolytic capacitors, the respective averages are calculated.

[0171] (c) ESR

[0172] After exposing the solid electrolytic capacitor to a high-temperature and high-humidity environment, the ESR is measured. More specifically, the solid electrolytic capacitor is left in a thermostat at 85°C and 85% RH for 1000 hours (high-temperature and high-humidity test). The solid electrolytic capacitor taken out from the thermostat is cooled to 20°C. Then, in an environment of 20°C, using a 4-terminal measurement LCR meter, the ESR (mΩ) of each solid electrolytic capacitor at a frequency of 100 kHz is measured. Then, the average value of the 20 solid electrolytic capacitors is calculated.

[0173] 《Solid Electrolytic Capacitors E2 and E3》

[0174] A total of 20 solid electrolytic capacitors E2 and E3 were fabricated according to the case of the solid electrolytic capacitor E1, and the same evaluations were performed. Among them, after the anode body with the first layer formed thereon was immersed in the second treatment liquid, it was taken out, dried at 100 °C for 3 minutes, immersed in distilled water for 5 minutes for water washing, and then dried at 100 °C for 3 minutes. Subsequently, the dried anode body was immersed in the third treatment liquid having the same composition as the first treatment liquid, taken out, and dried at 120 °C for a time of 10 minutes or more and 30 minutes or less. The immersions in the second treatment liquid and drying, water washing and drying, and immersions in the third treatment liquid and drying were repeated in sequence 4 times. In addition, in the solid electrolytic capacitor E2, the concentration of the salt in the second treatment liquid was 3.8 mass%.

[0175] 《Solid Electrolytic Capacitors E4 - E6》

[0176] A total of 20 solid electrolytic capacitors E4, E5, and E6 were fabricated according to the case of the solid electrolytic capacitor E1, and the same evaluations were performed. Among them, the number of times of alternately repeating the immersion in the second treatment liquid and drying and the immersion in the third treatment liquid and drying was 4 times in E4, 3 times in E5, and 2 times in E6. In addition, the concentration of the salt in the second treatment liquid was 3.8 mass% in E4, and 7.5 mass% in E5 and E6.

[0177] 《Solid Electrolytic Capacitors C1 and C2》

[0178] A total of 20 solid electrolytic capacitors C1 and C2 were fabricated according to the case of the solid electrolytic capacitor E6, and the same evaluations were performed. Among them, in C1 and C2, a surface modifier was not used in the preparation of the second treatment liquid. In addition, the number of times of alternately repeating the immersion in the second treatment liquid and drying, water washing and drying, and immersions in the third treatment liquid and drying was 2 times in C1 and 4 times in C2.

[0179] The results of the solid electrolytic capacitors E1 - E6 and C1 - C2 are shown in Table 1. E1 - E6 are examples, and C1 - C2 are comparative examples. The evaluation of the ESR after the high-temperature and high-humidity test is expressed as a relative value with the measured value in the solid electrolytic capacitor C2 set to 100.

[0180] [Table 1]

[0181]

[0182] As shown in Table 1, compared with C1 and C2 with an N / S ratio less than 0.30 and greater than 1.00, in E1 to E6 with an N / S ratio of 0.30 or more and 1.00 or less, the increase in ESR after the high-temperature and high-humidity test is significantly suppressed. In addition, from the viewpoint of suppressing the increase in ESR, the N / (C + O + S) ratio is preferably 0.033 or more and 0.050 or less. From the same viewpoint, the maximum thickness of the second part is preferably 15 μm or more and 42 μm or less.

[0183] The present invention has been described with respect to the current preferred embodiments, but such disclosure should not be construed in a limiting sense. Various modifications and changes will be apparent to those skilled in the art belonging to the technical field of the present invention from reading the above disclosure. Therefore, the appended claims should be construed to include all modifications and changes without departing from the true spirit and scope of the present invention.

[0184] Industrial Applicability

[0185] In the solid electrolytic capacitor of the present disclosure, an increase in ESR when exposed to a high-temperature and high-humidity environment can be suppressed. Thus, the solid electrolytic capacitor of the present disclosure can be used for various applications requiring high reliability and is also useful in applications requiring high heat resistance and applications used in a high-humidity environment. However, the uses of the solid electrolytic capacitor are not limited to these.

[0186] Description of Reference Numerals

[0187] 1: Solid electrolytic capacitor

[0188] 2: Anode body

[0189] 3: Dielectric layer

[0190] 4: Solid electrolyte layer

[0191] 5: Cathode lead-out layer

[0192] 5a: Carbon layer

[0193] 5b: Metal particle-containing layer

[0194] 11: Capacitor element

[0195] 12: Resin package

[0196] 13: Anode terminal

[0197] 13a: One end portion of the anode terminal

[0198] 13b: The other end portion of the anode terminal

[0199] 14: Cathode terminal

[0200] 14a: One end of the negative terminal

[0201] 14b: The other end of the negative terminal

[0202] 15: Negative electrode part

[0203] 16: Separation part

[0204] 17: Conductive adhesive

[0205] E1: The first end of the anode body

[0206] E2: The second end of the anode body

[0207] Ms: The main surface of the anode body

[0208] Es: The end face of the anode body

[0209] L1, L2: Straight lines formed by extending line segments corresponding to a pair of main surfaces of the anode body

[0210] CL: The center line of each main surface of the anode body

Claims

1. A solid electrolytic capacitor element, comprising: An anode body having a porous portion at least on the surface layer; A dielectric layer covering at least a part of the anode body; and A cathode portion covering at least a part of the dielectric layer, The cathode portion includes a solid electrolyte layer covering at least a part of the dielectric layer, The solid electrolyte layer contains nitrogen element N, sulfur element S, carbon element C and oxygen element O, and has: a first part filled into the pores of the porous portion of the anode body having the dielectric layer, and a second part protruding from the main surface of the anode body having the dielectric layer, The mass ratio of nitrogen element N to sulfur element S in the second part: N / S is 0.30 or more and 1.00 or less.

2. The solid electrolytic capacitor element according to claim 1, wherein, The mass ratio of nitrogen element N to the total amount of carbon element C, oxygen element O and sulfur element S in the second part: N / (C + O + S) is 0.033 or more and 0.050 or less.

3. The solid electrolytic capacitor element according to claim 1, wherein, The maximum thickness of the second part is 15 μm or more and 42 μm or less.

4. The solid electrolytic capacitor element according to claim 1, wherein, The anode body has an anode lead-out portion including a first end portion and a cathode formation portion including a second end portion, In a cross-section perpendicular to the direction from the first end portion to the second end portion of the solid electrolytic capacitor element at any position on the first end portion side of the solid electrolyte layer, the ratio of the thickness T1 of the second part formed at the corner portion of the anode body to the thickness T2 of the second part formed at the central portion of the anode body: T1 / T2 is 0.8 or more and 1.7 or less.

5. The solid electrolytic capacitor element according to claim 1, wherein, The cathode portion includes a cathode lead-out layer covering at least a part of the solid electrolyte layer, The cathode lead-out layer includes a metal particle-containing layer.

6. The solid electrolytic capacitor element according to claim 1, wherein, The second part includes a conjugated polymer and a dopant, The conjugated polymer includes monomer units corresponding to thiophene compounds, The dopant has a sulfo group.

7. A solid electrolytic capacitor, comprising at least one solid electrolytic capacitor element according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Manufacturing method of conductive polymer capacitor

    JP2009054925A

  • Method for manufacturing solid electrolytic capacitor

    WO2014087617A1